Analysis of the Application of Revenue and Expense Accounting at PT. Suka Mulia, a Public Transportation Service Company in Karo Regency - Beril Syahputra Ginting Suka; Milawati Br Ginting; Nenni Lestari Br Surbakti (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to analyze the implementation of revenue and Expense accounting in a public transportation service company, Suka Mulia, Karo Regency, and to assess its conformity with Statement of Financial Accounting Standards (PSAK) No. 1 concerning the Presentation of Financial Statements. The focus of the study is on the recording, recognition, and presentation of revenue and Expenses in the company’s financial reports. The research method used is a qualitative approach with a descriptive design. The results indicate that PT. Suka Mulia has not optimally implemented revenue and Expense accounting in accordance with PSAK Standards. Financial recording is still conducted in a simple manner using a cash basis and has not been prepared in the form of complete and periodic financial statements. Revenue is recorded based on daily cash deposits without classification by service type or accounting period, while operational Expenses such as fuel Costs, drivers’ salaries, vehicle maintenance, and asset depreciation are not systematically recorded under accrual principles. This condition causes the financial information produced to lack relevance, reliability, and comparability between periods. Based on these findings, it can be concluded that the implementation of revenue and Expense accounting at Suka Mulia, Karo Regency, is not yet in accordance with PSAK No. 1. This study recommends that the company begin applying an accrual-based recording system, classify revenue and Expenses in a structured manner, and prepare complete financial statements to improve the quality of financial information and support managerial decision-making.